Women, gender, remittances and development in the global South - Naerssen, A. L. van (Gender in a global/local world)
This book endeavours to take the conceptualisation of the relationship between transnational remittance exchanges and gender to a new level. Thus, inevitably, it provides a number of case studies of relationships between gender and remittances from around the world, highlighting different processes and practises. Thereby the authors seek to understand the impact of remittances on gender and gender relations, both at the sending as well as at the receiving end. For each case study authors ask how remittances affect gender identities and relationships but also vice versa. By itself this already adds a wealth of insights to a field that is remarkably understudied despite a volume of studies on gender and the feminization of migration in developing contexts. Chapters take an open, explorative approach to the relationship between gender and remittance behaviour with the aid of case studies focusing on transnational flows between migrants and countries of origin. With the wide variety of cases this book is able to provide conceptual insights to better understand how remittances affect gender identity, roles and relations (at both the receiving and sending end) and give specific attention to the roles of various actors directly and indirectly involved in remittance sending in current collectively organized remittance schemes from around the world.